1994
DOI: 10.1111/j.1365-2141.1994.tb04936.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble IL‐2 receptor levels in HCV‐infected haemophiliacs: a possible indicator of liver disease severity

Abstract: We have measured sIL-2R in 60 haemophiliacs and 20 male control subjects. Haemophiliacs were grouped according to their HIV/HCV antibody status. Group 1 (n = 20) comprised HIV + ve/HCV + ve, group 2 (n = 27) HIV - ve/HCV + ve and group 3 (n = 13) HIV - ve/HCV - ve. Group 4 comprised the normal control subjects. We also examined, retrospectively, the relationship between the severity of chronic liver disease, assessed histologically, and sIL-2R levels in selected patients. There was no significant difference be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Liver sinusoidal and inflammatory cells have been reported to be sources of IL-2 and no consensus exists on the predictive value of this cytokine. Apparently, expression of IL-2 is associated with a more advanced stage of disease, as previously reported (Makris et al 1994, Napoli et al 1996, Bozkaya et al 2000, Gramenzi et al 2005). In our sample, although a higher concentration of IL-2 was found in the serum, no significant expression was found in the liver from the cases compared to the normal controls.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Liver sinusoidal and inflammatory cells have been reported to be sources of IL-2 and no consensus exists on the predictive value of this cytokine. Apparently, expression of IL-2 is associated with a more advanced stage of disease, as previously reported (Makris et al 1994, Napoli et al 1996, Bozkaya et al 2000, Gramenzi et al 2005). In our sample, although a higher concentration of IL-2 was found in the serum, no significant expression was found in the liver from the cases compared to the normal controls.…”
supporting
confidence: 65%
“…IFN-γ is clearly augmented in the serum of chronic hepatitis C patients (Tilg et al 1992, Cacciarelli et al 1996, Kamal et al 2004) and its increase has been correlated with an increase in the severity of disease (Gonzalez-Peralta et al 1994). Moreover, an increased expression of IL-1, IL-2, IL-6, IL-10 and IL-18 has been documented in either the blood or liver of chronically HCV infected patients (Makris et al 1994, Schvoerer et al 2003, Hassan et al 1997, Oyanagi et al 1999, Polyak et al 2001. Nonetheless, most studies have been limited by a reduced sample size, resulting in a lack of statistical power.…”
Section: Abstract: Chronic Hepatitis C -Cytokines -Immunohistochemismentioning
confidence: 90%
“…Th1 cytokine responses activate T cells and macrophages important for host antiviral defense. Several studies have demonstrated increased soluble IL-2 receptor and IFN-␥ levels in the sera of patients with HCV infections (8,12). Progressive liver injury in HCV infection correlates with increased intrahepatic expression of Th1-type cytokines (17).…”
Section: Rtf Expression On Cd3mentioning
confidence: 99%
“…We therefore analyzed the intrahecesses may be occurring. 4 However, there is a paucity of patic messenger RNA (mRNA) expression of Th1-like (indata relating to the intrahepatic expression of cytokines that terleukin [IL]-2, interferon [IFN]-g) and Th2-like (IL-4, may be expected to mediate any immune response in the IL-10) cytokines in chronic hepatitis C patients (n Å 17) liver in chronic HCV infection. and controls (n Å 6) and correlated the results with liver Cytokines are regulatory molecules that play an important histology and intrahepatic viral load.…”
mentioning
confidence: 99%
“…We therefore analyzed the intrahecesses may be occurring. 4 However, there is a paucity of patic messenger RNA (mRNA) expression of Th1-like (indata relating to the intrahepatic expression of cytokines that…”
mentioning
confidence: 99%